Intercultural interaction experiences in a tertiary level institution in Malaysia - Krishnasamy, Hariharan N. (Elsevier Ltd., 2014)
This paper aims to investigate intercultural interaction experiences of international students and local instructors in an institution of higher learning in Malaysia, namely, Universiti Utara Malaysia.The interaction experiences focus on verbal communication only.A qualitative approach was used to elicit information on verbal communication and the challenges faced by the participants involved, which were the Arab students and Malay instructors.Data was collected in 2010/2011.The findings show that there are challenges that both parties face when communicating verbally.The understanding of challenges faced by communicators in intercultural encounters may provide useful pointers for developing intercultural communication competence.